Reconstructed variational iteration algorithm via third-kind shifted Chebyshev polynomials for the numerical solution of seventh-order boundary value problems - Christie Yemisi Ishola; Musiliu Tayo Raji; Mutiu Lawal Olaosebikan; Mfon Okon Etuk; Asimiyu Olalekan Oladapo; Aduragbemi Adekunle Victor (Mathematics and Computational Sciences, 2022)
The variational iteration algorithm using shifted Chebyshev polynomials of the third kind was used to obtain the numerical solution of seventh order Boundary Value Problems(PVBs) in this paper. The proposed method is made by constructing the shifted Chebyshev polynomials of the third kind for the given boundary value problems and used as a basis functions for the approximation. Numerical examples where also given to show the efficiency and reliability of the proposed method. Calculations were performed using maple 18 software.